Gambaran Tingkat Stres Akademik pada Mahasiswa Keperawatan STIKES Pasapua Ambon Tahun 2024 - Dodikrisno E Manery; Taufik Zuneldi; Yushar A Embisa; Abdul M Ukratalo; Nadira Pattimura (Jurnal Anestesi, 2024)
Academic stress is a common issue faced by students, particularly those in demanding programs such as nursing. This study aims to describe the level of academic stress among students at STIKES Pasapua Ambon. The researcher employed a descriptive quantitative method. The sample in this study consisted of 76 individuals. Data were collected by distributing questionnaires or surveys online using Google Forms. Data were analyzed using univariate analysis to provide a descriptive overview The results showed that the majority of respondents were female (68.4%), aged 17-19 years (46.1%), living in dormitories (36.1%), and from outside Ambon Island (68.4%), with academic stress levels falling in the moderate category (48.7%). Given the moderate academic stress experienced by many students, it is important to raise awareness about the importance of mental well-being.